2018
DOI: 10.1021/acsanm.8b01642
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Photocatalytic Applications of 2D Sheets of Nonlayered Manganese Telluride by Liquid Exfoliation

Abstract: Metal tellurides are highly sought after for energy and spintronic applications much of which is owed to its catalytic and magnetic properties. Confining it into twodimensions and improving the surface area enriches its catalytic activity and magnetic properties. Herein, we demonstrate the isolation of ultrathin two-dimensional sheets of manganese(II)telluride having an average thickness of ∼2 nm and flake size of ∼100 nm by means of liquid phase exfoliation presumably for the first time. Vanishing of exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 45 publications
(65 reference statements)
1
41
0
Order By: Relevance
“…The corresponding luminescence peak positions of the nanosheets of different thicknesses are around 1.3 eV, close to that obtained by peeling from the bulk. 19 We can also see that, as thickness of the sample decreases, the luminescence peak position has a slight shift from 1.28 to 1.31 eV, which is caused by the enhancement of the quantum confinement effect as the size decreases. 31 The information on the PL spectrum provides us with an idea to select materials with different band gaps by thickness, which can only be achieved with a few layers in other 2D materials, and is of great significance to the design of optoelectronic devices such as phototransistors in future.…”
Section: Resultsmentioning
confidence: 74%
“…The corresponding luminescence peak positions of the nanosheets of different thicknesses are around 1.3 eV, close to that obtained by peeling from the bulk. 19 We can also see that, as thickness of the sample decreases, the luminescence peak position has a slight shift from 1.28 to 1.31 eV, which is caused by the enhancement of the quantum confinement effect as the size decreases. 31 The information on the PL spectrum provides us with an idea to select materials with different band gaps by thickness, which can only be achieved with a few layers in other 2D materials, and is of great significance to the design of optoelectronic devices such as phototransistors in future.…”
Section: Resultsmentioning
confidence: 74%
“…MnTe is a typical polymorphism and stabilizes in hexagonal NiAs-type α-phase [nickeline (NC), Figure S1a] under normal atmospheric conditions, showing a phase change from α-phase to β-phase [wurtzite, Figure S1b], and then to γ-phase [zinc-blende, Figure S1c], and finally to δ-phase [salt-rock, Figure S1d] with the increase of temperature in the phase diagram. All of these MnTe phases exhibit antiferromagnetic (AFM) ground states. Recently, anisotropic magnetoresistance memory and magnetic anisotropy of α-MnTe have been reported to show the availability in AFM spintronic and memristive devices. , Thanks to the polymorphism, reversible resistive switching correlated to the reversible displacive transformation, which is between the α-phase (nickeline) and the β-phase (wurtzite), is found in MnTe and demonstrates a stronger competition in nonvolatile memory than in conventional phase-change Ge–Sb–Te materials . Interestingly, Balan et al reported the magnetic ordering transfer from the antiferromagnetic state to the paramagnetic one and the bandgap broadening from 1.3 to 2.1 eV when α-MnTe is confined to 2D form . In contrast, the metastable state γ-MnTe is of interest for optoelectronic devices because of its wide direct bandgap of 3.4 eV, ,, while α-MnTe has an indirect bandgap of 1.37–1.51 eV and CdTe has a direct bandgap of 1.50 eV .…”
Section: Introductionmentioning
confidence: 99%
“…17 Interestingly, Balan et al reported the magnetic ordering transfer from the antiferromagnetic state to the paramagnetic one and the bandgap broadening from 1.3 to 2.1 eV when α-MnTe is confined to 2D form. 22 In contrast, the metastable state γ-MnTe is of interest for optoelectronic devices because of its wide direct bandgap of 3.4 eV, 19,23,24 while α-MnTe has an indirect bandgap of 1.37−1.51 eV and CdTe has a direct bandgap of 1.50 eV. 6 γ-MnTe has been mentioned as a promising Cu-free back contact layer in CdTe film photovoltaic cells due to the wide gap and structural compatibility with CdTe.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides, Ajayan et al. [ 60 ] reported that the stripping of ultrathin 2D MnTe nanosheets had a size of ≈100 nm with a thickness of ≈2 nm by liquid‐phase exfoliation. O'Dwyer et al.…”
Section: Preparationmentioning
confidence: 99%
“…In addition, Ajayan et al. [ 60 ] reported that non‐layered 2D MnTe nanosheets were employed to sensitize TiO 2 nanotubes for photocatalytic water splitting under visible light irradiation. Li et al.…”
Section: Applicationsmentioning
confidence: 99%